Arterial Ischemic Stroke Prospective Study - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from Departments of Paediatric Neurology, Bristol Royal Hospital for Children, the Institute of Child Health, London, and other centers in the UK, conducted a prospective population-based study of 96 children aged 29 days to 16 years with radiologically confirmed arterial ischemic stroke (AIS) occurring over a 1-year period (July 2008 to June 2009) in southern England.